An exploratory analysis of new competencies: a resource based view perspective - Coates, Theresa Taylor; McDermott, Christopher M (Journal of Operations Management, 2002)
AbstractThe resource based view (RBV) theory of the firm widely acknowledges that capabilities that are unique and are important for achieving sustained competitive advantage. It has been argued in the manufacturing literature that manufacturing facilities, technology and policies are important to gain performance. However, little has been done to examine the capabilities from a resource based perspective. Nor has there been an exploration in how firms develop and leverage new capabilities. The literature also tends to neglect how complex and often intertwined these capabilities are within the firms. This study addresses this gap in the literature by examining the successful development of new resources and competencies that were created when Analog Devices developed an emerging technology. The paper is exploratory and identifies the new competencies and Analog Devices’ ability to capitalize upon them.